A Prospective Study of Lupus and Rheumatoid Arthritis in Relation to Deployment in Support of Iraq and Afghanistan: The Millennium Cohort Study. (4th September 2011) - Jones, Kelly A.; Granado, Nisara S.; Smith, Besa; Slymen, Donald J.; Ryan, Margaret A. K.; Boyko, Edward J.; Gackstetter, Gary D.; Phillips, Christopher J.; Smith, Tyler C.
Abstract : The objective of this study was to prospectively assess the association between deployment in support of the operations in Iraq and Afghanistan and newly reported lupus and rheumatoid arthritis while also considering the effects of demographic, behavioral, and occupational characteristics. A total of 77, 047 (2001–2003) and 31, 110 (2004–2006) participants completed the baseline Millennium Cohort questionnaire and were resurveyed approximately every 3 years. Longitudinal analyses were used to assess the adjusted association between deployment to Iraq and Afghanistan with and without combat exposures and newly reported disease. After adjusting, deployment was not significantly associated with newly reported lupus compared with nondeployers. However, compared with nondeployers, deployers with and without combat exposures were significantly less likely to newly report rheumatoid arthritis. Women, non-Hispanic black, and Hispanic participants had a significantly elevated risk for both diseases. Overall, deployment was not associated with an increased risk of newly reported lupus or rheumatoid arthritis.